Blurring the boundaries between an institutional repository and a research information registry: where’s the join? - Rumsey, S (2010)
Key motivations for provision of an institutional repository (IR) for research outputs within a higher education institution (HEI) are storage, retention, dissemination and preservation of digital research materials. Increasingly IRs are being considered as tools for research management as part of pan-institutional systems. This might include statutory reporting such as that required for the forthcoming UK REF (Research Excellence Framework). Such functionality generally requires integration with other management systems within the HEI. It is common to find that each research management system has been selected to serve a specific need within an organisational department, any broader aim being out of scope. As a result, data is held in many silos, is duplicated and can even be ‘locked in’ to those systems. This results in problems with data sharing, as well as lacks of efficiency and consistency. Some institutions are addressing this problem by considering CRISs (Current Research Information Systems) or business intelligence systems. The need for easy deposit in the institutional repository at the University of Oxford has prompted the development of a registry and tools to support research information management. Many of the motivations behind the repository are common with those for research information management. Not only do the two areas of focus have many common aims, but there is considerable overlap of design, data, services, and stakeholder requirements. This overlap means that the boundaries between the repository and the resulting tools being implemented for publicly available research activity data are blurred. By considering these two areas together with other related digital repository services, new opportunities and efficiencies can be revealed to the benefit of all stakeholders.